2017
DOI: 10.1002/chem.201703745
|View full text |Cite
|
Sign up to set email alerts
|

Size‐Dependent Reactivity of Nano‐Sized Neutral Manganese Oxide Clusters toward Ethylene

Abstract: Neutral manganese oxide clusters with the general composition Mn O (N=2-22; x=-1, 0, 1) with dimensions up to a nanosize were prepared by laser ablation and reacted with C H in a fast flow reactor. The size-dependent reactivity of C H adsorption on these clusters was experimentally identified and the adsorption reactivity decreases generally with an increase of the cluster size. Density functional theory calculations were performed to study the geometrical and electronic structures of the Mn O (N=1-6) clusters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 79 publications
0
6
0
1
Order By: Relevance
“…[23][24][25][26][27] By conducting investigations of metal cluster catalysis, extensive efforts have been made to improve the reaction activity, and it is recognized that the specific sizes and geometric/electronic structures of clusters are often crucial factors in determining the resulting mechanisms and reaction rates. [28][29][30][31][32][33] Also, the binding energies can fluctuate with increasing numbers of atoms, allowing clusters at a certain size to transform from a two-dimensional planar structure to a three-dimensional (3-D) structure (e.g., Pt 3 vs Pt 4 ), and occasionally leading to "magic" number species such as Al 13 − , Ag 13 − , and 12,[34][35][36] In many studies, clusters are supported on a selected substrate in order to evaluate the catalytic reactions in a practical way. The interaction between the metal clusters and support is a fundamental characteristic in heterogeneous catalysis and plays an essential role in elucidating the electronic structures, adsorption behavior, and catalytic activities.…”
Section: Introductionmentioning
confidence: 99%
“…[23][24][25][26][27] By conducting investigations of metal cluster catalysis, extensive efforts have been made to improve the reaction activity, and it is recognized that the specific sizes and geometric/electronic structures of clusters are often crucial factors in determining the resulting mechanisms and reaction rates. [28][29][30][31][32][33] Also, the binding energies can fluctuate with increasing numbers of atoms, allowing clusters at a certain size to transform from a two-dimensional planar structure to a three-dimensional (3-D) structure (e.g., Pt 3 vs Pt 4 ), and occasionally leading to "magic" number species such as Al 13 − , Ag 13 − , and 12,[34][35][36] In many studies, clusters are supported on a selected substrate in order to evaluate the catalytic reactions in a practical way. The interaction between the metal clusters and support is a fundamental characteristic in heterogeneous catalysis and plays an essential role in elucidating the electronic structures, adsorption behavior, and catalytic activities.…”
Section: Introductionmentioning
confidence: 99%
“…The VUV single photon ionization coupled with TOF-MS has been demonstrated to be essential for detecting neutral species . The reactivity of neutral oxide clusters of manganese, , cobalt, iron, , and vanadium ,, toward CO, C 2 H 4 , NH 3 , C 4 H 10 , and CH 3 OH has been studied in recent years. It was found that the products detected by VUV photoionization were generated directly from the reactions of neutral metal oxide clusters with small molecules.…”
Section: Discussionmentioning
confidence: 99%
“…After single photon ionization, the cluster ions passed through the reflector and then were detected by a dual microchannel plate detector. Note that most of the metal oxide clusters have ionization energies below 10.5 eV; , thus, most of them can be ionized and detected.…”
Section: Methodsmentioning
confidence: 99%